71 Barriers to providing optimal care to children with medical complexity in the emergency department: A physicians' perspective. (21st October 2022) - Alshammri, Fahd; Altamimi, Sarah
Abstract: Background: Children with medical complexity (CMC) are a subset of the pediatric population with chronic medical conditions requiring specialized care and high health resource utilization. Due to the nature of their underlying diseases, along with the medical devices that they are reliant on, they account for a large proportion of annual pediatric emergency department (ED) visits in tertiary centres and about one third of the children admitted. ED physicians are often the first to interact with CMC patients and thus the quality of care they provide influences the hospital course of those patients. Objectives: To determine and explore the barriers that ED physicians face when providing care to CMC in the ED and identify potential areas of improvement in care provided in the ED. Design/Methods: Semi-structured personal interviews were conducted virtually with 20 pediatric emergency medicine physicians and fellows. Each participant was asked the same set of questions and given extra time to elaborate. Interviews were transcribed verbatim and manual coding was conducted to identify commonalities across the interviews. Results: We identified four major themes and 12 sub-themes as barriers to optimal care of CMC in the ED. Major themes included time, training, medico-legal concerns, and care plans. The two most commonly identified barriers were time required to care for CMC patients, identified by 90% (n=18) of the participants, and limited exposure during fellowship training, identified by 80% (n=16) of the participants. Only 20% (n=4) identified medico-legal challenges as a unique barrier when managing CMC. All the participants (n=20) emphasized the importance of a care plan, a detailed document given to caregivers of CMC by the primary care team with details about their medical condition, and if not available, 85% (n=17) indicated that it will affect the efficiency and quality of care provided. Even if a care plan is available, 50% (n=10) of the participants would still contact the complex care team for further management recommendations. Conclusion: Care plan accessibility and time restraint in the ED are major barriers faced by PEM physicians in the ED when caring for CMC. Additional training during fellowship in complex care medicine and providing patients with an updated care plan are two interventions suggested to optimize care of CMC in the ED.